Phylogeny and historical biogeography of Gondwanan moss‐bugs (Insecta: Hemiptera: Coleorrhyncha: Peloridiidae). (10th April 2018) - Ye, Zhen; Damgaard, Jakob; Burckhardt, Daniel; Gibbs, George; Yuan, Juanjuan; Yang, Huanhuan; Bu, Wenjun
Abstract: The moss bugs of the Peloridiidae, a small group of cryptic and mostly flightless insects, is the only living family in Coleorrhyncha (Insecta: Hemiptera). Today 37 species in 17 genera are known from eastern Australia, New Zealand, New Caledonia and Patagonia, and the peloridiids are thereby a group with a classical southern Gondwanan distribution. To explicitly test whether the present‐day distribution of the Peloridiidae actually results from the sequential breakup of southern Gondwana, we provide the first total‐evidence phylogenetic study based on morphological and molecular characters sampled from about 75% of recognized species representing 13 genera. The results largely confirm the established morphological phylogenetic context except that South American Peloridium hammoniorum constitutes the sister group to the remaining peloridiids. A timescale analysis indicates that the Peloridiidae began to diversify in the land mass that is today's Patagonia in the late Jurassic (153 Ma, 95% highest posterior density: 78–231 Ma), and that splitting into the three extant well‐supported biogeographical clades (i.e. Australia, Patagonia and New Zealand/New Caledonia) is consistent with the sequential breakup of southern Gondwana in the late Cretaceous, indicating that the current transoceanic disjunct distributions of the Peloridiidae are best explained by a Gondwanan vicariance hypothesis.